Spindle cell/pleomorphic lipoma of the cheek: A case report. Issue 1 (27th March 2019) - Yoshida, Yu; Tamura, Takayuki; Takubo, Kazuko; Otsuki, Kazuma; Doi, Rieko; Kodani, Isamu
Abstract: We report a rare case of spindle cell/pleomorphic lipoma (SL/PL) in a 76‐year‐old woman who visited our hospital because of a mass on her right cheek. She presented with no other abnormal symptoms. We observed a 22‐mm wide, elastic, painless, yellow mass on her right cheek that was tumefactive, and the boundary between it and the surrounding tissue was relatively clear. With the patient under general anesthesia, we performed surgery to remove the tumor, which was identified by pathological examination as SL/PL. Six months postoperatively, the patient experiences no symptom recurrence and is in good condition.